Level 2 Diploma in Health and Social Care - Maclean, Siobhan; Harrison, Rob, 1976-; Bridge, Melanie; Gelhard, Elizabeth (2015)
This accessible textbook provides a wealth of information and advice for learners working towards the Level 2 Diploma in Health and Social Care (4222).
Includes bibliographical references and index.
Keywords: Social service -- Textbooks; Public health -- Textbooks; Society